(untitled) (Research, Society and Development, 2024)
The search for foods that combine flavor and nutritional benefits has gained prominence in the current food scene. In this context, yogurt, a product traditionally recognized for its health benefits due to the presence of probiotics, has been the subject of innovations. The constant consumption of artisanal foods such as yogurt is considered beneficial for maintaining health. Yogurts can be enriched with preparations based on fruit pulp in different ways: containing pieces of fruit in different sizes, without such pieces, with or without seeds, dyed with natural or synthetic dyes, and flavored. Brazil nuts are recognized for their richness in nutrients, such as selenium, unsaturated lipids and proteins. Studying its incorporation into dairy products can expand the nutritional profile and health benefits of the product. The objective of this work was to develop Gourmet Yogurt through Natural Fermentation Enriched with Brazil Nuts. The present work was carried out in the municipality of Beruri-am, with the aim of presenting an experiment in schools, gourmet yogurt, enriched with Brazil nuts. Analysis of the nutritional composition revealed that the enriched yogurt has significant levels of selenium, an essential mineral with antioxidant properties that contribute to cellular health. Furthermore, the presence of polyunsaturated fatty acids from Brazil nuts adds value to the product’s lipid profile, providing cardiovascular benefits. The presence of proteins, calcium, selenium and B vitamins was notable, standing out as a healthy option to strengthen bones, improve cardiovascular health and promote general well-being. Gourmet yogurt enriched with Brazil nuts is a healthy and tasty option that can be consumed by children and adults. The inclusion of gourmet yogurt enriched with Brazil nuts in school lunches can contribute to reducing childhood obesity, which is a growing problem in Brazil and around the world.